Secondhand Smoke, PEFR, And Pregnancy In The Second And Third Trimesters - Harahap, Huntari; Shafira, Nyimas Natasha Ayu; Enis, Rina Nofri; Kusdiyah, Erny; Firmansyah, Firmansyah; Nuriyah, Nuriyah (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2025)
Introduction: Pregnant women exposed to Secondhand Smoke (SHS) face a high risk of impaired lung function, which is naturally reduced by advancing pregnancy. This study analyzed the effect of SHS exposure on Peak Expiratory Flow Rate (PEFR) and its relationship with gestational age and key physiological parameters. Methods: This cross-sectional study involved 50 non-smoking pregnant women (Trimester II and III) exposed to SHS in Jambi City. PEFR was measured using a Peak Flow Meter. Statistical analysis used Pearson correlation and Chi-square tests (p<0.05). Results: All respondents (100%) showed significantly lower actual PEFR than predicted values, confirming a universal decline in lung function. A significant association was found between gestational age and PEFR (p<0.05), with the third trimester group having the most pronounced decrease (<320 L/minute). PEFR was not significantly correlated with blood glucose (r=0.089), hemoglobin (r=0.125), or SpO2​ (r=0.153). Conclusion: Decreased PEFR in pregnant women exposed to SHS is primarily linked to mechanical limitations from late gestational age, not metabolic or oxygen-carrying disturbances. Prevention of SHS exposure is crucial for maternal respiratory health.